A Parental Tool to Screen for Posttraumatic Stress in Children: First Psychometric Results. Issue 4 (28th July 2014) - Verlinden, Eva; van Laar, Yvette L.; van Meijel, Els P. M.; Opmeer, Brent C.; Beer, Renée; de Roos, Carlijn; Bicanic, Iva A. E.; Lamers‐Winkelman, Francien; Olff, Miranda; Boer, Frits; Lindauer, Ramón J. L.
Abstract: The Children's Revised Impact of Event Scale (CRIES‐13) is a brief self‐report measure designed to screen children for posttraumatic stress disorder (PTSD). This study investigates the psychometric properties of a Dutch version of the CRIES‐13–parent version and evaluates its correlation with the child version. A sample of 59 trauma‐exposed children (8 years–18 years) and their parents completed an assessment including the CRIES‐13 (child/parent version) along with the Anxiety Disorders Interview Schedule for DSM‐IV: Parent version. Results demonstrated good internal consistency (α = .87) with acceptable values for the 3 subscales. A strong correlation ( r = .73) with another measure of PTSD and lower correlations with a behavioral measure ( r = .15 to .38) were found, confirming the convergent/divergent validity. A cutoff score ≥ 31 emerged as the best balance between sensitivity and specificity, and correctly classified 83.6% of all children as having a diagnosis of PTSD. This study provides support for the reliability and validity of the CRIES‐13–parent version as a screening measure for posttraumatic stress in children.